Unveiling Positioning Nystagmus in Patients of Horizontal Semicircular Canal Benign Paroxysmal Positional Vertigo by Diagnostic Head-Shaking in the Yaw Plane - Vats, Ajay Kumar (Annals of Otology and Neurotology, 2019)
Introduction The diagnosis of benign paroxysmal positional vertigo (BPPV) is largely dependent on elicitation of positioning nystagmus on the diagnostic positional tests, namely Dix-Hallpike and supine roll tests (DHT and SRT, respectively), in patients complaining of vertigo, which occurs when patient’s head moves relative to the gravity. The pattern of elicited positioning nystagmus localizes as well as lateralizes the diseased canal, and the therapeutic positioning maneuver is accordingly undertaken.Objective The diagnostic positional tests, at times fail to elicit positional nystagmus, leaving clinician in a state of dilemma, when examining a patient who is currently experiencing paroxysms of vertigo triggered by positional change. In two patients with history consistent with BPPV but with negative positional tests initially, head shaking for 10 seconds in the yaw axis was done, and Dix-Hallpike and supine roll tests were repeated. The aim of head shaking for 10 seconds was to unveil positional nystagmus, to precisely localize and lateralize the diseased semicircular canal.Results and Discussion In the two cases of horizontal semicircular canal BPPV (HSC-BPPV) reported here, the DHT and/or SRT initially failed to elicit positional nystagmus but head shaking for 10 seconds in the left Dix–Hallpike position in case one and with the head anteflexed 30-degrees in the sitting position in the case two, unveiled horizontal positional nystagmus on ensuing SRT. The use of head-shaking in the yaw plane to unveil a horizontal positioning nystagmus in cases where a conventional positional test (DHT and SRT) has failed to elicit the PN, has not been reported in the literature hitherto.Conclusion After precise localization and lateralization of the diseased canal, both patients successfully underwent successful treatment with Gufoni maneuver. A verifying SRT done at 1 hour and/or at 24 hours follow-up was negative. In patients, who are currently experiencing paroxysms of vertigo triggered by the change of position of head relative to the gravity; head-shaking for few seconds just prior to the positioning test, can unveil positional nystagmus not elucidated with the conventionally performed positional tests.
Keywords: benign paroxysmal positional vertigo; Dix-Hallpike test; Gufoni maneuver; positional nystagmus; supine roll test